Market potential analysis for tengas (Neolissochilus sp.) in the Malaysian market - Ng, Xin Khai; Mohd Noh, Kusairi; Shuib, Ahmad; Mohamad Zainalabidin, Syahaneem; Mohamed Arshad, Fatimah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
There are some signals that Malaysian marine landings are decreasing and that wild stocks have been over-fished. However, it has extensive inland water bodies which have the potentials to be developed into freshwater aquaculture sites. Tengas (Neolissochilus sp.), a freshwater type of fish, are found in abundance in Malaysia; but has not reached the commercial level in the market. This paper examines the potential of developing tengas as a commercial freshwater species. The data used in this study were obtained through primary data search from key informants and a survey. A semi-structured open-ended questionnaire with Malay and Chinese languages was designed for the interviews. The study areas covered Peninsular Malaysia and East Malaysia. From the survey, we found that tengas has potential to be taken as a food item and an ornamental fish. The wild stock of tengas in fact is also worthwhile to be conserved for agro-tourism development. Many restaurant operators are willing to invent cooking method on tengas.